Paul decentered reading 2 Corinthians with the Corinthian women - Fox, Arminta M. (Lanham Boulder New York London Lexington Books, 2020)
"This book argues that the presence of women in the Christ communities of first-century Corinth changes how 2 Corinthians should be interpreted. Using a feminist approach to interpret the text, Arminta M. Fox presents readings that are ethically and historically viable. She examines how questions of community identity and leadership are situated within broader discourses of power in the Roman imperial and patriarchal contexts of the first-century Mediterranean world. By assuming the dialogical presence of strong and diverse women leaders in the community, Fox develops counter-readings to ones that assume Paul's singular authority. "--From back cover
This book argues that the presence of women in the Christ communities of first-century Corinth changes how 2 Corinthians should be interpreted. Using a feminist approach to interpret the text, Arminta M. Fox presents readings that are ethically and historically viable. She examines how questions of community identity and leadership are situated within broader discourses of power in the Roman imperial and patriarchal contexts of the first-century Mediterranean world. By assuming the dialogical presence of strong and diverse women leaders in the community, Fox develops counter-readings to ones that assume Paul's singular authority.
Revision of author's thesis (Ph. D.)--Drew University, 2015 under title: "You yourselves are our letter" : a feminist and decolonizing approach to 2 Corinthians
Literaturverzeichnis: Seite 183-196
Keywords: Paul -- the Apostle, Saint; Bible -- Feminist criticism; Bible -- Criticism, interpretation, etc; Women -- Biblical teaching; Paul; Bible; Feminist Criticism; Criticism, interpretation, etc; Hochschulschrift